Association Between 24-H Movement Guidelines and Cardiometabolic Health in Chilean Adults - De Moraes-Ferrari, G (Nature Research, 2022)
This study aimed to examine the association between meeting 24-h movement guidelines and cardiometabolic health in Chilean adults. We used cross-sectional data of 2618 adults from the Chilean National Health Survey 2016–2017. Meeting the 24-h movement guidelines was defined as ≥ 600 MET-min/week of physical activity; ≤ 8 h/day of sitting time; and 7 to 9 h/day of sleep duration. Cardiometabolic health indicators were body mass index, waist circumference, high triglycerides, high blood pressure, type 2 diabetes, metabolic syndrome, and risk of cardiovascular disease in a 10-year period. Meeting none out of three 24-h movement guidelines (vs all three) was associated with higher odds of overweight/obesity (OR 1.67; 95%CI 1.45 to 1.89), high waist circumference (1.65; 1.40 to 1.90), hypertension (2.88; 2.23 to 3.53), type 2 diabetes (1.60; 1.26 to 1.94), metabolic syndrome (1.97; 1.54 to 2.40) and risk of cardiovascular disease (1.50; 1.20, 1.80). Meeting one guideline (vs three) was associated with higher odds of five of out seven cardiometabolic indicators. Our study found that the composition of movement behaviors within a 24-h period may have important implications for cardiometabolic health. © 2022, The Author(s).